Influence of ageing treatment on work hardening behaviour of a Ni-base superalloy - Singh P.N.; Singh V. (My University, 2025)
Thus it may be summarised that work hardening behaviour of the alloy superni 263 can not be analysed using the simple power law equation. The work hardening behaviour is satisfactorily analysed using the modified power law equation (Ludwigson equation). There is systematic variation in the different work hardening parameters K1, n1, K2, n2 and εC with the period of ageing at 800°C. The drastic lowering of the parameters n1 and eup, from ageing even for a short duration, suggests that this material should be formed in fully solution treated condition and any precipitation of γ′ must be avoided for good formability.